Economic and Shariah Considerations in Debt Financing - Abozaid عبد العظيم (Journal of King Abdulaziz University: Islamic Economics, 2022)
This paper includes suggestions for minor amendments to the Zarqa’s paper, and for legal and economic analyzes of the reality of debt financing in financial institutions; regardless of their identity (i.e., Islamic, or conventional). After presenting these detailed comments on Zarqa’s research, the paper begins by answering questions raised by the journal’s editorial board. Through the answers, the paper compares normal deferred payment sales, i.e., those that take place outside the spectrum of financial institutions, with usury-based financing. It then compares debt financing (via financial intermediation) in Islamic financial institutions and usury-based financing. The paper shows that direct deferred payment sale differs in substance and effect from usury-based financing, while debt-based financing through financial intermediation, i.e., through Islamic financial institutions, leads to the same consequences as interest-based institutions in terms of the creation of excessive debts and its concentration in certain institutions, which makes these financial institutions susceptible to financial crises that can affect individuals, institutions and the overall economy. Thereafter, the paper examines the possibility of developing a practical financing structure that avoids the adverse effects of debt-based financing and distinguishes Islamic financing, in its essence and effects, from conventional financing. This structure can be found in the mode of diminishing Mushārakah, as this method of financing is supposed not to lead to the creation of debt. This paper, however, suggests significant modifications to this formula to ensure that it does not contribute to the creation of debt. The paper then concludes by outlining some challenges that may face the implementation proposed structure and highlighting ways to address them.